Плутоний для мафии: роман / Зорик Шохин - Шохин Зорик (Черная метка, 1998)
Экземпляры: ф.6 (1998) / Инвентарный номер: 40689 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ш 82 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44